2009
DOI: 10.1088/1742-6596/150/4/042151
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic susceptibility measurement under high pressure and magnetization measurement of S = 1/2 dioptase lattice antiferromagnet

Abstract: Abstract. Natural mineral Dioptase (Cu6Si6O18 · 6H2O) is an S=1/2 antiferromagnet with a unique spin network which consists of helical chains along the c axis connected by inter chain exchange interactions. In order to study the ground state of dioptase, we have performed the magnetization measurement for B//c (easy axis) at 1.5 K and have found the spin-flop transition at 13 T. Moreover, the pressure effect of the magnetic susceptibility is investigated up to 1.78 GPa using the SQUID magnetometer where TN inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 7 publications
4
5
1
Order By: Relevance
“…The magnetic properties of green dioptase have been reported by a number of authors [14,[16][17][18]20]. We have performed bulk characterization of our sample, and the results agree with those reported in Refs.…”
Section: A Bulk Propertiessupporting
confidence: 90%
See 3 more Smart Citations
“…The magnetic properties of green dioptase have been reported by a number of authors [14,[16][17][18]20]. We have performed bulk characterization of our sample, and the results agree with those reported in Refs.…”
Section: A Bulk Propertiessupporting
confidence: 90%
“…Early nuclear magnetoresonance (NMR) and specific-heat measurement indicated that it orders antiferromagnetically (AFM) below 21 K [12,13]. This is close to the results from the most recent susceptibility, specific heat, and neutron diffraction measurements reporting Néel temperatures of about 15 K [9, [14][15][16] and much lower than T N obtained from susceptibility measurements [17,18]. The ordered magnetic moment stemming from the Cu 2+ ions is reduced and equals to ∼0.4-0.5 μ B [9,15,18,19].…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…The field region of NMR is approximately 13.2 -13.7 T, which well falls within the field region of broad magnetization jump at H C = 13 (±1) T [9]. So, we consider that the result shown in Fig.…”
Section: Resultssupporting
confidence: 71%